A cross sectional study on awareness about cancer screening methods for breast and cervical cancer in women of reproductive age from Jhansi, Uttar Pradesh - Sharma, Sudha; Arya, Vimal K.; Malhotra, Anil K. (International Journal Of Community Medicine And Public Health, 2023)
Background: Non-communicable diseases (NCDs) are responsible for 63% of all deaths in India of which 9% are due to cancers according to the World Health Organization (WHO) global profile 2018. One in eight men and one in eleven women have a premature risk of dying from cancer before the age of 75. To reduce the morbidity and mortality due to the disease early diagnosis of disease and risk factors by regular screening of asymptomatic people is recommended. Objectives of the study were: to assess the awareness about methods for breast and cervical cancer screening among women of reproductive age, and to assess their readiness to go for screening. Methods: In a health awareness session on cancer screening among women of reproductive age the participants (104 women) were given a self-designed questionnaire which was administered before the session. The questionnaire covered general awareness about cancer, the symptoms and the methods of screening for breast and cervical cancer. The results were expressed in frequency and percentages. Results: The mean age of participants was 29.8 years (range 21 years-45 years). 88% felt that early diagnosis would improve outcome. Only 11% had heard of Pap test and only 3 had gotten it done. Around 21% had heard about mammography and only 4% had heard about breast self-examination. 86% and 90% were ready to get themselves screened for cervical cancer and breast cancer respectively, if given the opportunity. Conclusions: This study highlights both the lack of knowledge and the high acceptance of cancer screening among women. Awareness campaigns at regular intervals backed by immediate access to screening facilities are required to address the problem.